HETEROSIS AND COMBINING ABILITY STUDIES IN NEAR HOMOZYGOUS LINES OF OKRA [ABELMOSCHUS ESCULENTUS (L.) MOENCH] FOR GROWTH PARAMETERS - Y. A. LYNGDOH; R. MULGE; A. SHADAP (The Bioscan, 2013)
The present investigation was carried out with the objective of identifying good combiners and to assess the magnitude of heterosis for growth characters. Maximum heterosis was observed in the cross KO-2 × PK (48.20%) for plant height, KO-2 × AA (23.90%) for number of leaves, KO-6 × PK (-43.05%) for internodal length over the better parent and KO-6 × PK (56.07%) for plant height over commercial check, KO-2 × PK for number of leaves over the best parent (6.99%) and the commercial check (47.59%) and the crosses KO-6 × PK and KO-13 × V5 exhibited significant negative heterosis over the best parent (-10.42%) and the commercial check (-11.34%) for internodal length. The cross KO-2 × PK (19.28) for plant height, KO-2 × PK (6.31) for number of leaves, KO-5 × V5 for internodal length (-2.87) and number of branches per plant (0.60) and KO-4 × V6 (2.18) for number of nodes on the main stem were identified as good specific combiners. The parent KO18 (13.69) for plant height, KO-6 for number of leaves (1.43), internodal length (-1.13) and number of nodes on the main stem (1.37) and KO-12 (0.34) for number of branches per plant were identified as good general combiners. Non-additive gene action was predominant for most of the traits.